Onboard Model-based Prediction of Tram Braking Distance. Issue 2 (2020) - Do, Loi; Herman, Ivo; Hurák, Zdeněk
Abstract: In this paper, we document a design of a computational method for an onboard prediction of a breaking distance for a city rail vehicle—a tram. The method is based on an onboard simulation of tram braking dynamics. Inputs to this simulation are the data from a digital map and the estimated (current) position and speed, which are, in turn, estimated by combining a mathematical model of dynamics of a tram with the measurements from a GNSS/GPS receiver, an accelerometer and the data from a digital map. Experiments with real trams verify the functionality, but reliable identification of the key physical parameters turns out critically important. The proposed method provides the core functionality for a collision avoidance system based on vehicle-to-vehicle (V2V) communication.